Muscidae (Insecta: Diptera) of Argentina: revision of Buenos Aires province fauna, with a pictorial key to species - Patitucci, Luciano Damián (2013)
The knowledge of Muscidae of Argentina is fragmentary and incomplete. In this work, 43 species of Muscidae are recorded from Buenos Aires province, the largest and the most populated of Argentina. Redescriptions of Dolichophaonia trigona (Shannon & Del Ponte), Helina nivaloides Albuquerque, Mydaea sexpunctata (Wulp) are presented. Two new synonymies are proposed: Mydaea latomensis Snyder is established as a new junior  synonym of M. sexpunctata, and Neodexiopsis croceafrons Snyder is established as a new junior synonym of N. paulistensis Albuquerque. We designated lectotypes for Ophyra carbonaria Shannon & Del Ponte, Phyronota platensis Shannon & Del Ponte, Phyronota portensis Shannon & Del Ponte, and Spilogaster sexpunctata Wulp. Arthurella choelensis Patitucci & Mariluis, Limnophora aurifacies Stein, Lispe setuligera (Stein), Morellia (Trichomorellia) trichops (Malloch), Neomuscina zosteris (Shannon & Del Ponte), and Synthesiomyia nudiseta (Wulp) are recorded for the first time from Buenos Aires province, and Graphomya maculata (Scopoli) and Helina nivaloides are newly recorded from Argentina. New records of distribution for 21 of the 43 species herein studied are presented. A pictoric key to adults of the 43 species of Muscidae from Buenos Aires province is presented. Notes on biology, distribution in Argentina, and references in the literature for this family are also given.